2013
DOI: 10.1093/brain/awt310
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity as a predictor of response to treatment in first episode psychosis

Abstract: The integrity of brain white matter connections is central to a patient’s ability to respond to pharmacological interventions. This study tested this hypothesis using a specific measure of white matter integrity, and examining its relationship to treatment response using a prospective design in patients within their first episode of psychosis. Diffusion tensor imaging data were acquired in 63 patients with first episode psychosis and 52 healthy control subjects (baseline). Response was assessed after 12 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
108
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 47 publications
17
108
1
4
Order By: Relevance
“…On the contrary, at follow-up FA values were generally numerically higher. In line with 2 recent longitudinal studies over 12 weeks that indicated clozapine treatment 51 and mixed antipsychotic treatment 52 improved white matter integrity, our findings support that second-generation antipsychotics may protect against myelin degradation 19,20 or even improve myelination. [53][54][55] Specifically, and consistent with previous observations of functional hyperfrontality in patients with first-episode schizophrenia, our findings could indicate that selective dopamine D2/3 blockade regulate the NMDA receptors, which in turn reduce the putatively elevated and neurotoxic levels of glutamate associated with psychosis.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, at follow-up FA values were generally numerically higher. In line with 2 recent longitudinal studies over 12 weeks that indicated clozapine treatment 51 and mixed antipsychotic treatment 52 improved white matter integrity, our findings support that second-generation antipsychotics may protect against myelin degradation 19,20 or even improve myelination. [53][54][55] Specifically, and consistent with previous observations of functional hyperfrontality in patients with first-episode schizophrenia, our findings could indicate that selective dopamine D2/3 blockade regulate the NMDA receptors, which in turn reduce the putatively elevated and neurotoxic levels of glutamate associated with psychosis.…”
Section: Discussionsupporting
confidence: 90%
“…In a prospective design study, Reis Marques et al [61] found that non-responders showed lower FA than both responders and healthy control subjects mainly in the uncinate, cingulum and corpus callosum, whereas responders were indistinguishable from healthy control subjects. Interestingly, after 12 weeks of treatment, there was an increase in FA in both responders and non-responders that positively correlated with antipsychotic exposure, raising the possibility that antipsychotics may restore white matter integrity as part of the therapeutic response.…”
Section: Structural Connectivitymentioning
confidence: 99%
“…Conform the volumetric findings, neurodevelopmental decreased WM integrity in clinical high-risk populations 68,69 , as well as post-onset progression of widespread WM alterations in patients with late stage psychotic disorder 70 has been reported.…”
Section: Fa Course Over Timementioning
confidence: 60%
“…FA increase in mainly the uncinate, cingulum and corpus callosum in first-episode psychotic patients (n=42) after 12 weeks of antipsychotic treatment, whereas FA also positively correlated with AP exposure 68 and iv) widespread FA increase after 12…”
Section: Antipsychotic Medicationmentioning
confidence: 96%
See 1 more Smart Citation